Obcy w Dacji; rec. książki: Lucretiu Mihailescu-Birliba, Ex toto orbe Romano: Immigration into Roman Dacia. With Prosopographical Observations on the Population of Dacia - Mrozewicz, Leszek (Studia Europaea Gnesnensia, 2016)
.